A service evaluation of outcomes in two in-patient recovery units. (December 2017) - Macpherson, Rob; Calciu, Claudia; Foy, Chris; Humby, Kim; Lozynskyj, Dave; Garton, Charles; Steer, Hannah; Elliott, Helen
Abstract : Aims and method: To evaluate outcomes for patients during their admission or in the first year of treatment in two in-patient recovery units. Changes in health and social functioning, service use and need (rated by patients and staff) were evaluated. Results: In 43 patients treated, there was a large (30%) increase in patients discharged to their own tenancies, rather than supported accommodation. There was minimal change in Health of the Nation Outcome Scales (HoNOS) scores in the course of the admission but staff- and patient-rated unmet needs reduced and met needs increased. Needs changed mainly in domains relating to social functioning. Reductions in risk to self and others were rated by staff but not patients. There were no cases of patients being readmitted to acute hospital during the study period. Clinical implications: Although these results offer some support to the treatment approach described in these in-patient recovery units, further research in larger samples is needed to identify how these services can best be deployed to help individuals with severe mental illness and complex needs.